2021
DOI: 10.1371/journal.pone.0251036
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for urinary tract infections in the first year after renal transplantation

Abstract: Background The most common infections among renal transplant patients are urinary tract infections (UTI). Our main objective in this study is to determine the incidence of UTIs in patients who have undergone renal transplantation in our hospital, to identify the causative microbiological agents, risk factors and determine the effects of UTI on short-term graft survival. Methods Urinary tract infections, which developed within the first year of renal transplantation, were investigated. Patients were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
0
17
2
Order By: Relevance
“…In previous studies, it was reported that kidney functions returned to normal over time after an attack of UTI. 14,26 Olenski et al reported that patients with renal dysfunction during an UTI attack were improved their kidney function in the 2nd week after infection, and there was no difference in kidney functions 2 years later when compared to patients who did not develop UTI 4 . In our study, the 2nd year eGFR of patients who were developed UTI was found to be significantly lower when compared to patients who did not develop UTI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, it was reported that kidney functions returned to normal over time after an attack of UTI. 14,26 Olenski et al reported that patients with renal dysfunction during an UTI attack were improved their kidney function in the 2nd week after infection, and there was no difference in kidney functions 2 years later when compared to patients who did not develop UTI 4 . In our study, the 2nd year eGFR of patients who were developed UTI was found to be significantly lower when compared to patients who did not develop UTI.…”
Section: Discussionmentioning
confidence: 99%
“…UTI was accepted as the detection of >105 colony forming units (CFU/mL) of microorganism per urine milliliter and positive urine culture in patients with clinical symptoms of UTI 5,13 . A positive urine culture results detected in patients without clinical symptoms were accepted as asymptomatic bacteriuria (ABU) 5,14 . Recurrent urinary tract infection (R-UTI) was defined as a urinary tract infection that progressed with three or more symptomatic episodes in at least a 12-months period or two or more in any 6-months period 5,14 .…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with end-stage kidney disease (ESKD) receiving dialysis, kidney transplantation (KT) may have potential benefits in increasing the quality of life and decreasing the risk of mortality [ 1 ]. However, the risk of infection in recipients with KT may be high compared with that in the general public because of the continuous administration of intensive immunosuppressive drugs, and the main cause of mortality and morbidity is contagious bacterial disease [ 2 , 3 ]. Urinary tract infections (UTI) are the most common infectious diseases for KT patients—from 20 to 80% of KT patients develop UTIs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTI) are the most common infectious diseases for KT patients—from 20 to 80% of KT patients develop UTIs [ 4 , 5 ]. Various risk factors have been distinguished which increase the risk of UTI after KT [ 2 , 6 , 7 , 8 ]. These factors include older age, female sex, diabetes mellitus (DM), history of acute injection, delayed graft function, deceased donor KT, longer duration of dialysis, urological abnormalities, and timing of stent removal [ 2 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%